Sneathia vaginalis sp. nov. (Fusobacteriales, Leptotrichiaceae) as a replacement of the species 'Sneathia amnii' Harwich et al. 2012 and 'Leptotrichia amnionii' Shukla et al. 2002, and emended description of Sneathia Collins et al. 2001. Issue 3 (22nd March 2021) - Eisenberg, Tobias; Gronow, Sabine; Falgenhauer, Jane; Imirzalioglu, Can; Mühldorfer, Kristin; Rau, Jörg; Blom, Jochen; Fawzy, Ahmad; Glaeser, Stefanie P.; Kämpfer, Peter
Abstract : Members of the genus Sneathia are fastidious bacteria that predominantly colonise the female genital tract and are significantly associated with reproductive disorders and genital and neonatal disease. From a taxonomical perspective, the genus only comprises the species Sneathia sanguinegens . Numerous reports on a second species, ' Sneathia amnii ', have been published, but the name has never been validated. The same is the case for ' Leptotrichia amnionii ', which was previously shown to belong to the same species as ' Sneathia amnii '. We studied strains DSM 16631 T and DSM 16630, which have been identified and deposited as ' Leptotrichia amnionii ' previously. At the time of isolation, these strains were found to be most closely related to, but clearly different from, Sneathia sanguinegens based on 16S rRNA gene sequence similarities. Both strains proved to be almost indistinguishable from ' Sneathia amnii ' based on molecular, morphological and physiological traits. The 16S rRNA gene sequence analysis revealed that strain DSM 16631 T was assigned to the genus Sneathia with a sequence similarity of 95.47 % to Sneathia sanguinegens CCUG 41628 T, followed by type strains of Caviibacter abscessus (93.03 %), Oceanivirga salmonicida (92.68 %) and Oceanivirga miroungae (91.97 %) as the next closely related members of the Leptotrichiaceae . The novel species was also clearly differentiated from other related taxa by core genome phylogeny, average nucleotide and amino acid identities, in silico DNA–DNA hybridization and MALDI-TOF MS. With respect to chemotaxonomic and physiological patterns, strains DSM 16631 T and DSM 16630 were again highly similar to Sneathia sanguinegens . On the basis of these data, we propose the novel species Sneathia vaginalis sp. nov. with the type strain DSM 16631 T (=CCUG 52977 T =CCUG 52889A T ) and a second strain DSM 16630 (=CCUG 52976=CCUG 52888) that were both isolated from bloodstream infections in women with puerperal fever in France. The G+C content of the DNA of the type strain is 28.4 mol% and the genome size is 1.28 Mbp. Based on the observed extremely high similarities of genotypic and phenotypic traits of the novel proposed species to those reported for ' Sneathia amnii ', we recommend using this new name in all further publications on this taxon.